UJI AKTIVITAS ANTIPIRETIK EKSTRAK ETANOL KULIT JERUK MANIS (Citrus x aurantium L) TERHADAP TIKUS PUTIH (Rattus novergicus) JANTAN GALUR WISTAR YANG DIINDUKSI PEPTON 5% - Ratna Widyasari; Ratika Ratiningsih (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
Sweet orange peel (Citrus x aurantium L) contains flavonoids that are able to inhibit prostaglandins so they have activity as antipyretic. This study aims to test the antipyretic activity of orange peel (Citrus x aurantium L) against Wistar male rats induced by 5% peptone. This research is an experimental research with complete random design. The test animal used was Wistar male white rats as many as 15 tail with 150 - 200 g weight. The test animals were divided into 5 groups: negative control (1% NaCMC suspension), positive control (paracetamol suspension) and the test group were orange peel extract (Citrus x aurantium L) with concentration of 0.5%, 0.75% and 1%. Temperature measurements were performed before peptone 5%, 1 hour after peptone 5% and 30 min after treatment until 240 min. Data obtained were analyzed using anova test and LSD (Least significant different) test. The conclusion of this study is that the extract of sweet orange peel ethanol (Citrus x aurantium L) has antipyretic activity in Wistar male white rats and at 1% concentration has activity ability as antipyretic.